On-field concurrent validity of flight time-based countermovement jump height during fatigue: A comparison between inertial measurement units worn at different locations on the body - de Ruiter, C. J.; Haller, S.; van den Hoff, T. J.; Wilmes, E. (Journal of Sports Sciences, 2024)
We explored the feasibility of utilizing immediate changes in flight time-based vertical countermovement jump height as an on-field measure for fatigue-induced decrements in performance. Comparing Inertial Measurement Units (IMUs) worn at five body locations (feet, shorts for thighs and pelvis, waist strap, and thorax in a standard GPS vest) with a force plate as a reference, we enlisted 19 amateur football players who performed a series of 10 maximal 30 m sprints (initiated every minute). Maximal jumps were executed immediately before and after each sprint, with the latter jumps recorded on a force plate integrated into the field. Bland Altman`s bias (-0.49 cm) and limits of agreement (1.01 cm) were minimal for the feet IMUs. The thorax IMU had the highest bias (-6.35 cm), but the limits of agreement (2.73 cm) were similar to the other locations. Repeated measures correlations (rmcorr) between force plate and IMUs were excellent for the feet (rmcorr = 0.98) and good for the thorax (rmcorr = 0.86) and other locations except for the waist strap. In the fatigued state, within-session coefficients of variation ranged from 4.0% (pelvis in shorts) to 6.5% (waist strap). These findings suggest that body-worn IMUs possess the potential for a prompt and straightforward on-field vertical jump assessment to monitor acute fatigue.